2012
DOI: 10.1063/1.4721898
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of small Atwood number Rayleigh-Taylor instability using the magnetic levitation of paramagnetic fluids

Abstract: Experiments that take advantage of the properties of paramagnetic liquids are used to study Rayleigh-Taylor (RT) instability. A gravitationally unstable, miscible combination of a paramagnetic salt solution and a nonmagnetic solution is initially stabilized by a magnetic field gradient that is produced by the contoured pole-caps of a large electromagnet. Rayleigh-Taylor instability originates from infinitesimal random background noise with the rapid removal of current from the electromagnet, which results in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In experimental procedures there is inevitably some memory of initial conditions, as large wavelength perturbations of the order of the dimensions of the container will be present (Youngs 1984;Dalziel 1993;Snider & Andrews 1994). Experiments of two-layer RTI with widely varying experimental procedures have found a value of α that is around 0.07 (Dalziel 1993;Tsiklashvili et al 2012), although other experimental studies have found values that are somewhat lower, e.g. 0.057 (Dimonte et al 2004).…”
Section: Comparison With Experimentsmentioning
confidence: 95%
See 2 more Smart Citations
“…In experimental procedures there is inevitably some memory of initial conditions, as large wavelength perturbations of the order of the dimensions of the container will be present (Youngs 1984;Dalziel 1993;Snider & Andrews 1994). Experiments of two-layer RTI with widely varying experimental procedures have found a value of α that is around 0.07 (Dalziel 1993;Tsiklashvili et al 2012), although other experimental studies have found values that are somewhat lower, e.g. 0.057 (Dimonte et al 2004).…”
Section: Comparison With Experimentsmentioning
confidence: 95%
“…Many authors now believe that this is due to differences in initial conditions (e.g. Dalziel et al 1999;Tsiklashvili et al 2012), although another suggested explanation for the variation in α is the difference in Schmidt number (Sc = ν/D, where ν is the kinematic viscosity and D is the mass diffusivity) between experiments and numerics (Glimm et al 2001). In experimental procedures there is inevitably some memory of initial conditions, as large wavelength perturbations of the order of the dimensions of the container will be present (Youngs 1984;Dalziel 1993;Snider & Andrews 1994).…”
Section: Comparison With Experimentsmentioning
confidence: 97%
See 1 more Smart Citation
“…White et al (2010) used a paramagnetic substance in a strong magnetic field to place the fluids in an unstable configuration. The same technique was used by Huang et al (2007) and Tsiklashvili et al (2012). RTI experiments were also conducted in a high-energy-density environment using the NOVA laser to test the applicability of available theories at these extreme conditions (Remington et al 1994;Budil et al 1997).…”
Section: B Akula and D Ranjanmentioning
confidence: 98%
“…For small amplitude perturbations of an idealized gas-liquid interface, inviscid linear theory suggests an unbounded exponential growth, where different scales grow independently of one an- other. However, viscous effect may prevent from high wavenumber growth [3,14,58,60]; as a result, a 'most unstable' mode of solution is produced, which may be seen from the mechanical energy equation below. As the perturbations grow in a two-dimensional RTI, the gas-liquid interface deforms into counter-rotating rolls in the form of vorticity filaments.…”
Section: Viscous Effect On Rti At a Fixed Atwood Number A = 05mentioning
confidence: 99%